Outbreak of New Delhi Metallo-Beta-lactamase Carbapenemase Producing Enterobacterales on a bone marrow transplant unit: Role of the environment. Issue 2 (June 2021) - Prescott, Katherine; Billam, Harriet; Yates, Carl; Clarke, Mitch; Montgomery, Ros; Staniforth, Karren; Vaughan, Natalie; Boswell, Tim; Mahida, Nikunj
Abstract: Background: Carbapenemase Producing Enterobacterales (CPE) are a global health concern. Nosocomial outbreaks have been reported globally with patient-to-patient transmission felt to be the most frequent route of cross-transmission. Aim: To describe the investigation and control of an outbreak of healthcare-associated New Delhi Metallo-beta-lactamase (NDM) CPE on a haematology ward, over 2 months. Methods: Four patients acquired CPE; all had gastrointestinal tract colonisation with two subsequently developing bacteraemias. The outbreak team performed a retrospective review, prospective case finding and environmental sampling using swabs, settle plates, air and water sampling. Immediate control measures were implemented including appropriate isolation of cases and additional ward cleaning with chlorine disinfectant, ultra-violet light decontamination and hydrogen peroxide. Findings: Following two cases of nosocomial acquired CPE prospective case finding identified two further cases. 4.6% of the initial environmental samples were positive for CPE including from waste water sites, the ward sluice and the ward kitchen. Three of the four CPE isolates were identical on pulse field gel electrophoresis (PFGE) typing. Detection of the CPE from the ward kitchen environmental samples suggests a possible role for cross transmission. Conclusion: This is the first CPE outbreak report to highlight the role of a ward kitchen as a possible source of cross-transmission. In view of this we suggest ward kitchens are reviewed and investigated in nosocomial CPE outbreaks.